DETERMINANTS OF FRAUDULENT FINANCIAL REPORTING IN MINING COMPANIES: PENTAGON THEORY FRAUD PERSPECTIVE - Yanto, Alif Faruqi Febri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The purpose of this research is to find empirical evidence the influence of the fraud pentagon which consists of pressure, opportunity, rationalization, competence and arrogance on Fraudulent Financial Statements. The research method used in this study is multivariate analysis using the Generalized Structured Component Analysis tool. The research population is manufacturing companies in the mining sector listed on the Indonesia Stock Exchange for the 2017-2021 period with a total sample of 60 companies. This study shows that pressure, opportunity and competence have a significant effect on fraudulent financial statements, while rationalization and arrogance have no significant effect on fraudulent financial statements.